(untitled) (International Journal of Engineering and Computer Science, 2018)
The proposed paper gives LSB Information Hiding algorithm which can lift wavelet transform image. The idea behind the LSB algorithm is to insert the bits of the hidden message into the least significant bits of the pixels. Achieving the purpose of information hiding with the secret bits of information to replace the random noise, using the lowest plane embedding secret information to avoid noise and attacks, making use of redundancy to enhance the sound embedded in the way nature to be addressed. The results showed that the proposed algorithm has a very good hidden invisibility, good security and robustness for a lot of hidden attacks.However, the limitation of capacity has led us to think about an improved approach which can be achieved through hardware implementation systems with the help of a programmable gate array (FPGA) board. Watermarking is the process of embedding data within the domain of another data, this data can be text, image, audio, or video contents. MATLAB is used to convert video into images and then convert it into pixel-format i.e header files. Here to implement this paper XPS & VB are needed. In XPS do the hardware & software configuration. Then XPS could be processed by adding source and header files & converting into bit streams and download into FPGA, to obtain Secret image. The final result is shown on VB.